Special Testimony as a Reforming Concept in the Indonesian Juvenile Criminal Justice System - Khairil Anam; Rusmilawati Windari (Arena Hukum, 2024)
Children who have suffered from sexual violence face an increased risk of re-victimisation during judicial proceedings. A study by Hannah (2019) and Nina Papalia (2021) indicated that approximately 50% of child victims experience re-victimisation during trials, as they are required to relive their traumatic experiences. Countries like Norway and Brazil have introduced additional preventive measures to mitigate these negative effects. This normative study utilises statutory, conceptual and comparative approaches, aiming to examine the regulations governing the testimony of child victims of sexual violence in Indonesia, Norway and Brazil. Additionally, it seeks to identify positive aspects that could enhance Indonesia’s juvenile justice system. The findings suggest that Brazil’s ‘Special Testimony’ model for child testimony is more suitable for adoption in Indonesia than the ‘Nordic Model’ used in Norway. The ‘Special Testimony’ approach that could be integrated into Indonesia’s juvenile justice system includes (1) conducting investigations with electronic recording, which can be used as evidence in court; (2) having testimony examined by a psychologist or investigator trained in child psychology; (3) limiting a child’s testimony to a single occurrence during the investigation stage, unless deemed necessary by the judge; and (4) utilising technology or electronic devices during special examinations by a psychologist in a designated interview room.